'Locally acquired foreign accent' (LAFA) in contemporary Ghana. Issue 2 (22nd May 2013) - SHOBA, JO ARTHUR; DAKO, KARI; ORFSON‐OFFEI, ELIZABETH
ABSTRACT The term 'LAFA' stands for 'locally acquired foreign accent' and refers to a style of speech popularly known in Ghana as 'slurring'. It emerged in the 1990s, as a mainly phonological approximation to American speech, among young Ghanaians who may have never been to the US. The 'target' variety for English in the Ghanaian education system remains, as a colonial legacy, officially although not always in practice, British English. This paper reports a small‐scale study of often ambivalent attitudes towards LAFA, among tertiary level students, and as observed on public websites. The analysis situates LAFA within a theoretical framework of identity construction through linguistic choices. By using LAFA, speakers bid for membership of an imagined global community. However, they also flout essentialised expectations of their speech, apparently rejecting aspects of their linguistic repertoire acquired in earlier life. The benefits LAFA users aspire to are thus accompanied by some risk of social rejection and accusations of fakery.